PROFIT SHARING SYSTEM ON PURSE SEINE FISHING GEAR IN OCEAN FISHING PORT BELAWAN NORTH SUMATERA - Hamdani Rezki; Hendrik Hendrik; Arief Hazmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in July 2018 at the Belawan Ocean Fishing Port, Bagan Deli Village, Medan Belawan Sub-District, North Sumatra Province, about the system for purse seine.This research aims to find out the application of the profit sharing and wage system received by fishermen owners and cultivating fishermen in purse seine business.The method used in this study was a survey method with a total of 42 fishermen purse seine. The results showed that the profit sharing system of purse seine anchored in Belawan PPS was after deducting production costs, for Mini Purse Seine vessels 67.9% for owner fishermen and 32.1% for labor fishermen. The most revenue from the profit sharing of mini purse seine is the income of the owner's fishermen totaling IDR.54,447,900, - per trip while the least income from the profit sharing of the business is the ABK's income of IDR. 1,718,800, - per trip. While Big Purse Seine ships are 67,6% for owner fishermen and 32.4% for labor fishermen. The income that is the most from the profit sharing of big purse seine is the income of the owner's fishermen totaling IDR. 105,600,200 - per trip while the income that is the least from the profit sharing of big purse seine is the income of the crew amounting to IDR. 2,111,600, - per trip. In the fishery profit sharing system law no.16 in 1964 laborers obtained a minimum of 40% of the net proceeds and for fishermen the owner gained 60%. If UUBHP No. 16 of 1964, the income of the labor fishermen per trip for the Seine Mini Purse is IDR.2,548,000 per person. Whereas the owner fishermen get Rp. 48,141,000, -. For Seine Big Purse ships the income that should be received by labor fishermen is an average of IDR. 3,328,500, - per person, while the owner fishermen get IDR. 93,760,500, -.  Keywords: Fisherman Revenue, Local Revenue Sharing, Revenue Sharing According to UUBHP